2022
DOI: 10.3389/fonc.2022.1018767
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating effect of reovirus on immune checkpoint inhibition in microsatellite stable colorectal cancer

Abstract: The majority of colorectal cancers (CRCs) are microsatellite stable (MSS) and resistant to immunotherapy. The current study explores the possibility of using oncolytic reovirus to sensitize MSS CRC to immune checkpoint inhibition. While reovirus reduced metabolic activity among KRASMut cells, microarray/computational analysis revealed microsatellite status-oriented activation of immune-response pathways. Reovirus plus anti-PD-1 treatment increased cell death among MSS cells ex vivo. Reduced tumorigenicity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Pelareorep, a proprietary isolate of the reovirus Type 3 Dearing strain, has shown varied efficacy in treating melanoma, glioblastoma, colorectal, lung, and ovarian cancers ( 71 ). Although much of the therapeutic capacity of reoviruses is attributed to their ability to selectively replicate in and lyse RAS-transformed cells, several studies have demonstrated the ability of oncolytic viruses to trigger the host immune system against infected tumor cells, which could augment tumor elimination ( 22 , 26 28 ). It was further shown that reovirus anti-tumor activity is mediated through the activation of innate and adaptive host immune systems through dendritic cells, NK cells, and effector T-cells ( 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelareorep, a proprietary isolate of the reovirus Type 3 Dearing strain, has shown varied efficacy in treating melanoma, glioblastoma, colorectal, lung, and ovarian cancers ( 71 ). Although much of the therapeutic capacity of reoviruses is attributed to their ability to selectively replicate in and lyse RAS-transformed cells, several studies have demonstrated the ability of oncolytic viruses to trigger the host immune system against infected tumor cells, which could augment tumor elimination ( 22 , 26 28 ). It was further shown that reovirus anti-tumor activity is mediated through the activation of innate and adaptive host immune systems through dendritic cells, NK cells, and effector T-cells ( 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reovirus treatment enhanced the memory response of the immune system (25). Altogether, it has been shown that reovirus significantly alters the immune response towards the tumor (22,(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%